Unravelling the contribution of glial cells for the neuroinflammatory milieu of epileptic-like organotypic slices - Carvalho, Mafalda Cagica Pinto de (2021)
Tese de mestrado em Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2021